The significance of management information systems for enhancing strategic and tactical planning - Karim, Akram Jalal (2011)
Management Information Systems (MIS) is the key factor to facilitate and attain efficient decision making in an organization. This research explores the extent to which management information systems implemented to make successful decisions at two selected financial organizations. The research examined whether the selected financial institutions of Bahrain vary as to the use of Management Information Systems leadership of decision making for strategic and tactical planning purposes. The research adapted the quantitative research design to examine two research hypotheses. A total of 190 forms were equally distributed to those who are working at different management levels at the selected organizations. The results of the research showed that MIS was primarily used to enhance strategic planning in both financial institutions. The regression analysis revealed that Tactical planning is found to have no effect on Decision Making, while Strategic planning has a clear effect on the Decision Making Effectiveness in both organizations.